Pengembangan Startup dengan Pemanfaatan Teknologi di IIB DARMAJAYA - Melda Agarina; Susanti Susanti; Hendra Kurniawan; Yusminar Yusminar; Muhammad Ariza Eka Yusendra; Stefanus Rumangkit; Sutedi Sutedi; Edi Edi Pranyoto (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
Higher education is a party that can be the driving force or driving force for the emergence of young entrepreneurs. This is because tertiary institutions will strengthen mental attitudes, provide academic support, and social support to students to become entrepreneurs. In addition, universities provide knowledge to students about the sciences of becoming entrepreneurship. One of the universities that is trying to create young entrepreneurs based on technology or technopreneurs is the Darmajaya Institute of Informatics and Business (IIB Darmajaya). Regarding the progress of entrepreneurship in the Darmajaya IIB campus environment, the lecturer team who is also a community service team submitted a grant from the Ministry of Research, Technology and Higher Education's DRPM (Entrepreneurship Development Program) 2019-2021 program. This program is used as one of the flagship programs at the Darmajaya IIB campus as a means of increasing interest and the number of young entrepreneurs. The method of implementing PPK (Entrepreneurship Development Program) activities, namely: Understanding of technopreneurship, provision of tenant skills regarding technopreneur skills and development teams, product prototypes, making business plans and initial product / service presentations, incubation process to complete products / services, product launching and become a starup company. The results of the PPK activities carried out were the formation of six best tenants, namely: Essa Solution, Recycle_Indonesia, Informatika Ganesha, Beauty Start, Kutilang, IGE.Net